(untitled) (Agricultural Engineering, 2022)
The research was aimed at reducing the power consumption for grain cleaning by using energy-saving modes in the electromechanical systems of grain cleaning units. Specific consumption of active energy per production unit was adopted as a criterion for assessing energy-saving operation modes. The applied method of mathematical experiment planning (MEP) reduced the number of experiments to a minimum to obtain a reliable mathematical model of the research object. To determine the optimal specific power consumption, a theoretical method was developed to rebuild the mathematical model. Thus, the minimum specific power consumption of grain cleaning production lines was obtained, which allowed developing science-based rates of power usage that allow energy savings up to 8-10%.